OVERVIEW OF PATIENTS SATISFACTION LEVEL AT DENTAL CLINIC CIMAHI TENGAH HEALTH CENTER INDONESIA - Marlin Himawati; Kemala Rengganis; Rabiatul Adawiyah; Dhiya Fasya; Ulfah Rosida; Nunuk Fitriyana (Journal of Health and Dental Sciences, 2021)
Puskesmas represents the functional organization unit that runs health efforts accepted and affordable by the entire community with society's active role. Puskesmas must have a good quality of health service to provide the satisfaction of the patients. Patient satisfaction is one of the leading indicators of health facilities and has become a standard measure of quality-of-service customer satisfaction. The general objectives of the study are to evaluate the level of satisfaction of patients at the Dental Clinic of Puskesmas Cimahi Tengah, Cimahi City, based on tangible, reliability, responsiveness, assurance, and empathy. This study used a descriptive study method through a questionnaire about patient satisfaction toward services at the dental clinic of Puskesmas Cimahi Tengah. The sample size used in this study were all patients who came to the dental clinic of Puskesmas Cimahi Tengah. The study results are based on the five dimensions analyzed, namely tangibles, reliability, responsiveness, assurance, and empathy, which refer to the SERVQUAL model developed by Parasuraman. The service quality of the dental clinic at Puskesmas Cimahi Tengah on the dimensions of tangibles, reliability, responsiveness, assurance, empathy was very satisfying. The conclusion based on the analysis of the respondents' responses on patient satisfaction at the dental clinic at the Central Cimahi Center was very gratifying. DOI : 10.54052/jhds.v1n2.p197-208